Perceptions of supportive organizational practices and well-being among LGBQ+ employees - Perpich, Rachel A., author; Fisher, Gwenith, advisor; Gardner, Danielle, committee member; Graham, Daniel, committee member; Chen, Adela, committee member (Colorado State University. Libraries, 2024)
The increasing number of workers who identify with the LGBTQ+ community illuminates a pressing question regarding how organizations are navigating and implementing DEI initiatives to support minority identities. As organizational efforts to support and retain the rising population of sexual minority workers continue, it is additionally necessary to understand how these employees perceive such practices. The purpose of the current study is to examine the relationships between perceptions of supportive organizational practices, perceived organizational support, and worker well-being among LGBQ+ employees. Participants included 352 LGBQ+ individuals recruited via Prolific who completed online surveys at two time points. I hypothesized that LGBQ+ employees who reported their organization having supportive organizational practices would perceive more support from their organization, and thus have more favorable reports of well-being. Additionally, I expected sexual orientation identity centrality to moderate the relationship between perceptions of LGBQ+ supportive practices and general perceptions of organizational support. Results show support for all hypothesized relationships besides those including anxiety symptoms. Specifically, LGBQ+ employees who reported more favorable (i.e., higher) perceptions of LGBQ+ supportive practices also perceived more general support from their organization, which ultimately served as a mechanism for higher reports of job satisfaction and work-life balance and lower reports of depressive symptoms. Additionally, the relationship between perceptions of LGBQ+ supportive organizational practices and perceptions of general organizational support was stronger for employees who identified their sexual orientation as more central to their identity. The present study contributes to a growing body of literature on sexual orientation and work by providing empirical support for the relationship between LGBQ+ employees' perceptions of workplace practices, overall perceptions of support, and important indicators of worker well-being, including job satisfaction, mental health, and work-life balance. Theoretical and practical implications and recommendations for future research are discussed.
Keywords: LGBQ employees; perceived organizational support; organizational practices; employee well-being